Academic Career Development in Indonesia and the United Kingdom: A Systematic Literature Review - Kurniawati, Maya; Saleh, Choirul; Muluk, M.R. Khairul (Jurnal Pendidikan Indonesia, 2021)
Lecturers are an essential element of a higher education institution. The lecturer has two functions in Indonesia, namely an educator and a researcher who has the job in developing and deploying science, technology, and art to the community through the Three Pillars of Higher Education activities: education, research, and community services. This study aims to investigate and answer the three research questions, which involve how the academic career development system for lecturers, how the academic career development patterns for lecturers, and the factors which affect the academic career in Indonesia and the United Kingdom (UK). We chose the UK since it is one of the countries with the most robust higher education system globally. This research was required to capture the gap in academic career development for lecturers in Indonesia and the UK. There are 23 journal articles and other literature included and found using systematic literature review and PRISMA protocol. These journal articles and other literature analyzed by meta-synthesis and could describe the comparative perspectives between an academic career in Indonesia and the UK. These review results can be an excellent comparison for improving higher education systems, specifically in the academic career development for Indonesian lecturers. A significant improvement will encourage universities in Indonesia to embrace the vision as a world-class university.